Development Of A Quality By Design Framework For Oral Solid Dosage Forms (Atorvastatin Calcium Ir) Using In-Silico Risk Assessment And Design Space Prediction. - Akhani, Parth; Singh, Shubham; Rathi, Sanjesh (Journal of Neonatal Surgery, 2025)
A comprehensive Quality by Design (QbD) framework was developed for Atorvastatin Calcium immediate-release (IR) tablets, integrating systematic in-silico risk assessment and design space prediction. Atorvastatin calcium, classified as a BCS Class II HMG-CoA reductase inhibitor, presents significant formulation challenges owing to its low aqueous solubility and dissolution-limited absorption. The Quality Target Product Profile (QTPP) and Critical Quality Attributes (CQAs) were defined in line with ICH Q8(R2), followed by identification of Critical Material Attributes (CMAs) and Critical Process Parameters (CPPs) through Failure Mode and Effects Analysis (FMEA) risk scoring. A 2 Fractional Factorial screening design (16 runs) and Central Composite Design (CCD) implemented in Design Expert® established empirical factor–response relationships. Mechanistic dissolution modeling using DDDPlus™ and physiologically based pharmacokinetic / biopharmaceutics modeling (PBPK/PBBM) using GastroPlus® enabled virtual bioequivalence assessment. A robust design space was established: disintegrant level 3–5 % w/w, compression force 1800–2300 lbf, and API particle size 20–40 µm. Virtual bioequivalence trials confirmed Cmax ratio 98.9 % (90 % CI: 91–105 %) and AUC0–t ratio 99.1 % (90 % CI: 93–107 %), both within the 80–125 % acceptance limits. The integrated QbD–in-silico approach provides a science-based, clinically relevant design space and control strategy for Atorvastatin calcium IR tablets consistent with ICH Q8(R2), Q9, and Q10 guidelines..